2013
DOI: 10.4161/cc.25100
|View full text |Cite
|
Sign up to set email alerts
|

A role for p38 in transcriptional elongation of p21CIP1in response to Aurora B inhibition

Abstract: Aurora kinases play important functions in mitosis. They are overexpressed in many cancers and are targets for anticancer therapy. Inhibition of Aurora B results in cytokinesis failure and polyploidization, leading to activation of the p53 tumor suppressor and its target genes, including p21. The pathways that mediate p21 activation after Aurora B inhibition are not well understood. In this study, we identified a role for the p38 MAP kinase in activation of p21 when Aurora B is inhibited. We show that p38 is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…One study showed that p38 MAPK stabilizes p21 mRNA (22). Another study reported that p38 MAPK can enhance p21 expression by promoting the transcriptional elongation (23). USP22 acts upstream of p21 and represses p21 expression (4) and the present results indicate that expression of the p38 MAPK promoter p21 may take place partially through USP22 downregulation.…”
Section: A C Bsupporting
confidence: 53%
“…One study showed that p38 MAPK stabilizes p21 mRNA (22). Another study reported that p38 MAPK can enhance p21 expression by promoting the transcriptional elongation (23). USP22 acts upstream of p21 and represses p21 expression (4) and the present results indicate that expression of the p38 MAPK promoter p21 may take place partially through USP22 downregulation.…”
Section: A C Bsupporting
confidence: 53%
“…This allows for rapid induction of p21 after p53 activation. We have recently shown that induction of p21 after inhibition of Aurora B depends on p38 MAPK signaling (10). We found that p38 is not required for stabilization of p53 or for binding of p53 to the p21 promoter but that it instead promotes transcriptional elongation of p21 by RNA Pol II in response to Aurora B inhibition.…”
mentioning
confidence: 78%
“…Aurora B Are Dependent on p38 Signaling-We and others have recently shown that inhibition of the mitotic kinase Aurora B results in induction of the CDK inhibitor p21 (8,10,(21)(22)(23)(24)(25). Experiments with pharmacological inhibitors, isogenic cell lines, and specific siRNAs demonstrated that induction of p21 in response to Aurora B inhibition requires p53 as well as the MAPK p38 (10).…”
Section: A Subset Of P53 Target Genes Induced After Inhibition Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] In recent studies, the activation of p38 MAPK has been suggested to be induced by Aurora B kinase inhibition. 37,38 However, the role of p38 MAPK in VX680-induced effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%